Cover Image. Issue 4 (22nd January 2021) - Rundquist, Sara; Sachs, Michael C.; Eriksson, Carl; Olén, Ola; Montgomery, Scott; Halfvarson, Jonas
Abstract : The cover image is based on the Original Article Drug survival of anti‐TNF agents compared with vedolizumab as a second‐line biological treatment in inflammatory bowel disease: results from nationwide Swedish registers by Sara Rundquist et al., https://doi.org/10.1111/apt.16193 .